Human Capital Factors Affecting Human Resource (HR) Managers' Commitment to HR and the Mediating Role of Perceived Organizational Value on HR. Issue 2 (20th November 2015) - Oh, In‐Sue; Blau, Gary; Han, Joo Hun; Kim, Seongsu
Abstract: Human resource (HR) managers' commitment to their occupation (HR) leads to the proper delivery and implementation of HR practices and, therefore, is deemed as a critical factor for the success of HR practices. Based on sociocognitive, human capital, and signaling theories, this study examines: (a) HR managers' own and their chief HR officer's (CHRO) HR‐specific human capital as antecedents of their commitment to HR, and (b) the mediating mechanism through which the CHRO's HR‐specific human capital positively influences HR managers' commitment to HR. Based on 146 HR managers from 146 organizations in South Korea, the findings of the current study suggest that HR managers with higher levels of HR‐specific human capital and those working with CHROs with higher levels of HR‐specific human capital tend to have higher levels of commitment to HR. In addition, CHROs with higher levels of HR‐specific human capital positively influence HR managers' commitment to HR by signaling to them that HR and its function are valued and cared about by their organizations. Theoretical and practical implications of this study are discussed along with study limitations and further research directions. © 2015 Wiley Periodicals, Inc.